THE NEW GENERATIONS: CHALLENGES FOR SCHOOL PSYCHOLOGY AND PSYCHOLOGICAL COUNSELING - Drugas, Marius Ioan (Psychological thought, 2025)
In a rapidly evolving global landscape marked by technological innovations, cultural transformations, and socio-political shifts, the developmental contexts of children and adolescents are undergoing profound changes. This paper explores the unique psychological profiles, learning preferences, and mental health needs of Generation Z (born ~1997–2012) and Generation Alpha (born 2013 onward), highlighting the growing challenges faced by professionals in school psychology and psychological counseling. As digital natives, these generations exhibit heightened digital literacy, a preference for visual and interactive learning, and an increased awareness of mental health issues. However, they also face increased vulnerability to anxiety, depression, and social comparison – primarily due to excessive digital exposure. School psychologists and counselors must navigate an increasingly complex landscape involving diverse family structures, evolving educational needs, and resistance to traditional therapeutic models. This paper underscores the need for adaptive, culturally competent, and technology-integrated practices to effectively engage with Gen Z and Alpha. The April 2025 issue of Psychological Thought aimed to put together practical solutions and multidisciplinary perspectives, and offer evidence-based recommendations for practice and future research to support the mental health and learning needs of these new generations.